Unveiling the Financial Impact of Sustainability: A Comprehensive Analysis of ESG Scores and Their Relationship with Corporate Performance - Senhaji, Omar; Mateu-Bartolomé, Guillermo (Journal of Environmental Accounting and Management, 2026)
In this paper, we examine how environmental, social, and governance (ESG) strategy affects company's financial performance. Businesses have increasingly prioritized ESG factors as public concern about social inequality and climate change has grown. However, the extent of this impact on financial performance remains disputed. While some studies suggest a positive relationship, others argue for potential adverse effects, or no significant effects at all. Using French listed companies as data points, this research explores the joint and independent effects of the three ESG pillars on corporate financial performance, integrating rational choice theory to provide a fresh perspective in this academic debate. We found a statistically significant negative relationship between governance scores and financial performance, while the environmental and social scores have no significant effect. Overall, this study offers empirical evidence on ESG strategies to guide decision-making in sustainable business practices and policy formulation.